Acute ileitis facilitates infection with multidrug resistant Pseudomonas aeruginosa in human microbiota-associated mice. Issue 1 (December 2017) - Klitzing, Eliane; Ekmekciu, Ira; Bereswill, Stefan; Heimesaat, Markus
Abstract Background The rising incidence of multidrug resistant (MDR) Gram-negative bacteria includingPseudomonas aeruginosa has become a serious issue in prevention of its spread particularly among hospitalized patients. It is, however, unclear whether distinct conditions such as acute intestinal inflammation facilitateP. aeruginosa infection of vertebrate hosts. Methods and results To address this, we analysedP. aeruginosa infection in human microbiota-associated (hma) mice with acute ileitis induced by peroralToxoplasma gondii challenge. When perorally infected withP. aeruginosa at day 3 post ileitis induction, hma mice displayed higher intestinalP. aeruginosa loads as compared to hma mice without ileitis. However, the overall intestinal microbiota composition was not disturbed byP. aeruginosa (except for lowered bifidobacterial populations), and the infection did not further enhance ileal immune cell responses. Pro-inflammatory cytokines including IFN-γ and IL-12p70 were similarly increased in ileum and mesenteric lymph nodes ofP. aeruginosa infected and uninfected hma mice with ileitis. The anti-inflammatory cytokine IL-10 increased multifold upon ileitis induction, but interestingly more distinctly inP. aeruginosa infected as compared to uninfected controls. Immune responses were not restricted to the intestines as indicated by elevated pro-inflammatory cytokine levels in liver and kidney upon ileitis induction. However, except for hepatic TNF-α levels, P. aeruginosa infection did not result in more distinct pro-inflammatory cytokine secretion in liver and kidney of hma mice with ileitis. Whereas viable intestinal bacteria were more frequently detected in systemic compartments such as spleen and cardiac bloodof P. aeruginosa infected than uninfected mice at day 7 following ileitis induction, P. aeruginosa infection did not exacerbate systemic pro-inflammatory sequelae, but resulted in lower IL-10 serum levels. Conclusion Acute intestinal inflammation facilitates infection of the vertebrate host with MDR bacteria includingP. aeruginosa and might also pose particularly hospitalized patients at risk for acquisition. Since acuteT. gondii induced inflammation might mask immunopathology caused byP. aeruginosa, a subacute or chronic inflammation model might be better suited to investigate the potential role ofP. aeruginosa infection in the aggravation of intestinal disease.